Responsabilidade fiscal: análise dos gastos com pessoal nos municípios da região metropolitana de Fortaleza - Avelino, Vanessa dos Santos (2019)
After the implementation of the Real Plan in 1994, the federal government sought to increase its control over the public finances of local governments and one of the mech-anisms used was the LRF. Its approval came at a time when society demanded greater efficiency and practice of responsible fiscal management from the public manager at all levels of government and to frame the subnational spheres in the intended fiscal adjustment. The Fiscal Responsibility Law (LRF) represented a new benchmark for public finances in Brazil. Personnel expenses represent relevant amounts in the public accounts in order to make up a considerable portion of the budget and may jeopardize the resources allocated to investments. This research has as main purpose to analyze personnel expenses in the Metropolitan Region of Fortaleza-MRF from 2008 to 2017. For this purpose, the participation of personnel expenses in relation to the net current revenue of each municipality of the MRF will be evaluated; and verified if the amounts spent on personnel change as a function of revenue collected. This research has a qualitative approach: of qualitative nature, considering that it seeks to interpret the in-formation and data related to the object of the study; and descriptive, concerned with observing the facts, recording them, and analyzing them. A bibliographical research was done on the theoretical references already analyzed and published, and docu-mental research. Data collection was carried out mainly in the municipality's transpar-ency portal, in fiscal management reports, in municipal management monitoring re-ports and in the Ceará statistical yearbook. The study showed that of the 19 munici-palities studied, 84% of them exceeded, at some point in the historical series, the legal limit allowed with personnel expenses. The year 2015 was the most critical, when 47% in municipalities did not comply with the law. In 2017, this percentage decreased slightly, reaching 42%, concluding, therefore, that some municipalities of the RMF are realizing expenses with personnel above the legal limit allowed.